Development of Physic Problems for The Final Assessment in High School Level with Rasch Model Analysis - Maulana, Slamet; Supriyati, Yetti; Astra, I Made (Unnes Science Education Journal, 2020)
The aim of this research is to develop Physics problems that are appropriate to be used for the final assessment at High School level with Rasch Model Analysis. Research method used in this study is Research and Development with the ADDIE model. Physics problems developed refers to the USBN blueprint issued by BSNP. Problems that have been developed will be validated by Physics experts, then tested on students, and analyzed for their quality using Rasch Model analysis. Validation results from Physics experts gave a score of 86.25% with very good criteria, it shows that Physics problems are feasible in terms of Physics material. The problems that have gone through the validation stage are then tested to several students and analyzed using the Rasch Model. Results of the analysis show that problems that have been developed have good validity and reliability. Problems that have been developed also have varying degrees of difficulty. Results of this analysis also show that problems that have been developed are not biased for a certain group. Based on the results, it can be concluded that Physics problems that have been developed are appropriate to be used for the final assessment at High School level.